Descriptive Study Of Value Chain For Creating Competitive Benefits In The Rattan Industry - Evi Yuniarti; Anita Kusuma Dewi; Lihan Puspo R (Jurnal Ilmiah ESAI, 2013)
The objective of this research is to make deep analysis of how the cluster of rattan industry managed their activities using value chain strategy. This is important because of value chain analysis, both activities which have or have not been of great value to the company's competitive advantage can be identified. By doing this analysis, how the company's resources are integrated into a competitive advantage can be seen as well. The results showed that the average value of the respondents in the rattan industry Natar South Lampung, the main activity is high. The average value of the respondents' perception of the owners Â showed rattan industry in Natar South Lampung, the terms of support activity is at the average level.Key words: value chain, rattan , competitive, advantage